A comparative framework to support an ecosystem approach to fisheries in a global context - Emma M. Lockerbie (Resilience Alliance, 2020)
Although an ecosystem approach to fisheries has been recognized as a means of progressing toward sustainable fishing, successful implementation of this approach has been limited. However, one way in which progress has been made is through the use of suites of indicators. Decision tree frameworks can be used to incorporate trends in ecological, fishing, and environmental indicators into ecosystem assessments. A relatively generic decision tree framework has been developed and successfully applied to multiple ecosystems. This framework incorporates trends in indicators, as well as the impacts of fishing pressure and environmental variability on ecological indicators in order to assess the state of each ecosystem. The inclusion of ecosystem expert knowledge from the outset ensures trends are correctly interpreted and allows analyses to contribute to global comparisons in a robust and meaningful manner. Although ecological and environmental indicators are well developed, those addressing the human dimensions of marine ecosystems are less so. This framework holds the potential to incorporate such indicators in order to fully assess marine ecosystems in a comparative context. Such assessments could help ensure food security from marine resources into the future as well as ensuring the well-being of coastal communities. Here critical review of the potential value of this framework has been conducted, with its usefulness emphasized in the similarities it holds, and in the contribution it could make, to current global methods of ecosystem assessments.